Determining the strain to fracture for simple shear for a wide range of sheet metals. (December 2018) - Roth, Christian C.; Mohr, Dirk
Highlights: Demonstrated the risk of tensile fracture in flat shear specimens. Analyzed specimen validity for wide range of materials from low to high hardening and ductility. Evaluated performance of more than 600 specimen geometries. Recommend testing of three specimens to identify the strain to fracture for simple shear. Abstract: There is a particularly high degree of experimental uncertainty associated with the determination of the strain to fracture for simple shear. In most shear specimens, different stress states coexist and it is usually impossible to prove experimentally that fracture indeed initiated in the sheared zones. Peirs' simple shear specimen is analyzed in detail for nine generic materials covering different combinations from low to high strain hardening and from low ductility to high ductility. It is found that the validity of the shear fracture strain measurement depends on the strain hardening capability and the ductility of the material being tested, with a higher likelihood of validity for low hardening and low ductility materials. An extensive parametric study evaluating more than 600 distinct specimen geometries is performed in an attempt to identify a universal specimen geometry. It turns out that no single geometry exists which provides reliable measurements for all types of materials. While a single geometry can be found for different hardening behaviors, it seems to be necessary to use several distinct geometries to cover all levels of ductility. Since the ductility is usually not known prior to testing, we recommend testing three different types of specimen per material, reporting the highest measured strain among all specimens as strain to fracture for simple shear. Experiments are performed on specimens extracted from aluminum AA2024-T351, as well as DP800 and DP980 dual phase steels to demonstrate the validity of the proposed experimental methodology for identifying the strain to fracture for simple shear. Graphical abstract: Image, graphical abstract